(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article focuses on the issues of forming a culture of interethnic communication in future students and their understanding of their position and views as independent individuals. In developing a culture of interethnic communication in students, students’ experiences of entering into dialogue with representatives of other nationalities are also considered. This article serves as a source for the principle of a phased sequence of technologies for preparing future teachers to form a culture of interethnic communication